The THE EFFECT OF GROUP COUNSELING SERVICES USINGEXPRESSIVE WRITING TECHNIQUES REDUCING ACADEMIC STRESS ON INTROVERT STUDENTS: PENGARUH LAYANAN KONSELING KELOMPOK DENGAN TEKNIK EXPRESSIVE WRITING DALAM MEREDUKSI STRES AKADEMIK PADA SISWA INTROVERT - Melinda Yuwanka; I Wayan Dharmayana; Mayang T. Afriwilda (UNIVERSITAS BENGKULU, 2024)
The purpose of this study is to investigate the influence of group counseling services utilizing expressive writing techniques on the stress academic performance of introverted students. An experiment with a one-group pretest-posttest design is used in this study. The research population of class VIII students at SMP Negeri 22 Bengkulu City was 57 students. Then the sample was determined using a purposive sampling technique, totaling 9 students. Data were collected using inventories and Likert scale questionnaires. The research results show a value of t = 6.236 (p<0.05), which means that there is an influence of group counseling services with expressive writing techniques in reducing the academic stress of introverted students. Keywords: academic stress, group counseling, expressive writing techniques